Effect of sulphanilic acid on portland cement - Singh V.K.; Narang K.K.; Ali M.M. (My University, 2025)
The effect of sulphanilic acid on the setting of Portland cement has been investigated and it has been observed that with the increasing concentration of sulphanilic acid from 0.5 to 3.0%, the setting time of cement increases. The strength of 1:3 cement/sand mortar containing the above additive, decreases slightly on seven days. The workability of the above mix increases with the increasing amount of the additive and thus decreasing the water requirement. © 1979 Taylor & Francis Group, LLC.